The potential effect of silver nanoparticles to inhibit microbial activity in orthodontic adhesive appliances: A literature review - Silviana, Nur Masita; Fariha, Safira; Permata, Shevya Nanda Indika; Utomoputri, Tasya Safina; Pramadita, Thessalonica; Sukadi, Zefanya Nicko (Universitas Muhammadiyah Yogyakarta, 2024)
Silver nanoparticles have been the focus of research in various areas of dentistry, including orthodontics. Orthodontic treatment requires a long period of time, so the brackets are in the oral cavity for a long time. This can potentially trigger the formation of white spot lesions because plaque sticks more easily to the surrounding enamel. Using silver nanoparticles mixed with orthodontic adhesives has been reported to increase antibacterial and antimicrobial characteristics. This literature review aims to investigate the effect of adding silver nanoparticles to orthodontic adhesive devices in inhibiting antimicrobial activity. This study method was carried out by searching the online electronic databases PubMed, Science Direct, and Google Scholar with the keywords